Logical-semantic definition of a production process digital twin - A. V. Rechkalov; A. V. Artyukhov; G. G. Kulikov (Российский технологический журнал, 2023)
Objectives. A methodology currently being developed for generalizing and presenting knowledge about studied subject-oriented areas is based on a “model hypothesis” for determining the distinguished objects and their relationships. Such system models can be used in any information system to define the knowledge about subject-oriented areas. Systems engineering methods already make it possible to create information models of real objects supplemented by virtual components, and vice versa, i.e., models of virtual objects supplemented by real components. So, for example, the availability of information models of technological and production facilities and their connections with real equipment allow the creation and management of real-virtual production processes (PP) in accordance with Industry 4.0 methodologies. From a theoretical aspect, the development of system models of objects and their connections in subject-oriented areas is based on the problem of a formal consistent description (grammatical calculus) of the functional regularities of a given set of objects and their relationships. The purpose of the study is to develop an approach and principles of methodology for system modeling of production facilities and their connections to provide closed-loop control (forecasting, planning, accounting, regulation, etc.) in the production environments of machinery enterprises taking the form of their digital twins (DTs).Methods. The basic provisions of the theory of sets and graph theory—in particular, the provisions of the theory of categories of sets—are used according to the formal logic and control theories. System Engineering methods are also applied in the organization and management of machinery production.Results. The approach to the formation of a metastructure of production process digital twin (PPDT) based on the models of production facilities and their relationships is substantiated. The procedure and rules for constructing a PPDT system model are developed along with an approach to the structural and parametric identification of DT models, taking logical and semantic restrictions into account.Conclusions. A presented example for identifying the basic set of objects of the organization of the PPDT based on the logical-semantic analysis of production activities and the provisions of the unified standards of the unified system for technological preparation of production of machinery production as a researched subject area confirms the main provisions of the proposed methodology for constructing the PPDT.